Bipolar membrane and preparation method thereof

By using mesh hydrophilic modification and multi-layer structure coating technology during the preparation of bipolar membranes, the problems of large swelling and insufficient working conditions of existing bipolar membranes are solved, and higher mechanical strength, lower transmembrane voltage and longer service life are achieved, reducing energy consumption and operating costs.

CN119701665AActive Publication Date: 2025-03-28QUZHOU LANRAN NEW MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510238999.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-03-28
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

During use, existing bipolar membranes have problems such as large swelling and insufficient working conditions, resulting in short life and high energy consumption.

Method used

A bipolar film was prepared by hydrophilic modification of mesh cloth. By laying a hydrophilic mesh cloth on the PET film and uniformly coating the male film and the female film on it, a multi-layer structure bipolar film was formed. This method enhances the bonding force between the mesh support material and the positive layer and the negative layer, and reduces the permeability and transmembrane voltage of the anion permeability through the positive layer.

Benefits of technology

It improves the service life and mechanical strength of the bipolar membrane, reduces the transmembrane voltage and energy consumption, enhances the applicability of working conditions, and effectively reduces operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701665A_ABST
    Figure CN119701665A_ABST
Patent Text Reader

Abstract

The invention relates to a bipolar membrane and a preparation method thereof. The preparation method comprises the following steps: hydrophilic modification of screen cloth; spreading hydrophilic mesh cloth on a PET film, uniformly coating the mesh cloth and the PET film with the cation membrane slurry, and drying to obtain a partially sulfonated cation membrane; spraying the catalyst layer slurry on the positive membrane and drying to obtain a positive membrane with a catalyst layer; the slurry of the catalyst layer contains partial chloromethylated polystyrene, a toughening polymer, single secondary amine containing double bonds, single secondary amine without double bonds, an initiator and a dehydrating agent; uniformly coating the catalyst layer of the positive membrane with negative layer slurry, drying, and separating the PET film after drying to obtain the bipolar membrane; the negative layer slurry contains part of chloromethylated polystyrene, a toughening polymer, mono-tertiary amine containing double bonds, mono-tertiary amine containing no double bonds and an initiator; and transforming the bipolar membrane. The bipolar membrane is clear in interface of each layer, low in transmembrane voltage, high in mechanical strength, high in product percent of pass and stable in size in the using process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ion exchange membranes, and in particular relates to a bipolar membrane and a preparation method thereof. Background Art

[0002] The bipolar membrane is a composite membrane formed by bonding a cation exchange membrane and an anion exchange membrane, and has the function of producing the following so-called hydrolysis phenomenon: by applying voltage to both sides of the bipolar membrane immersed in an aqueous solution, the water in the membrane is dissociated into protons and hydroxides; utilizing this function, the bipolar membrane is combined with a cation exchange membrane and an anion exchange membrane to perform electrodialysis, thereby, for example, producing acids and bases from neutral salts.

[0003] There are two main types of bipolar membranes on the market, one is a monolithic bipolar membrane and the other is a composite bipolar membrane. Monolithic bipolar membranes are generally made by impregnating a thin film with monomers or filling a porous base membrane with monomers, polymerizing into a base membrane containing benzene rings, then sulfonating one side and aminating the other side, and then post-processing. Composite bipolar membranes are generally made by first polymerizing a supporting mesh with monomers to form a positive layer or a negative layer, and then coating the negative layer or the positive layer accordingly to make a bipolar membrane. The two bipolar membranes have their own advantages and disadvantages. Because the monolithic bipolar membrane is formed in one piece, the bonding between the positive and negative layers is good, and it is highly applicable under various working conditions. However, because there is no high-strength supporting material, the swelling during use is relatively large, which will affect the service life; although the composite bipolar membrane has a high-strength supporting material and small swelling, it is not suitable for use under specific working conditions.

[0004] In view of the advantages and disadvantages of the above two bipolar membranes, if the advantages of the two can be integrated, then a bipolar membrane with small swelling, stable size and strong applicability to working conditions can be produced. This membrane has a long life and a lower transmembrane voltage, which is beneficial to reduce energy consumption and effectively reduce operating costs. Summary of the invention

[0005] Based on the above-mentioned shortcomings and deficiencies in the prior art, one of the objects of the present invention is to at least solve one or more of the above-mentioned problems in the prior art. In other words, one of the objects of the present invention is to provide a bipolar membrane and a preparation method thereof that meet one or more of the above-mentioned requirements.

[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A method for preparing a bipolar membrane comprises the following steps: (1) Hydrophilic modification of the mesh to obtain a hydrophilic mesh; (2) Laying the hydrophilic mesh on the PET film, evenly coating the cationic membrane slurry on the mesh and the PET film, and drying to obtain a partially sulfonated cationic membrane; The cation membrane slurry is partially sulfonated polystyrene, and the dehydrating agent is completely dissolved in a good solvent; (3) spraying a catalytic layer slurry on the partially sulfonated cationic membrane and drying the slurry to obtain a cationic membrane with a catalytic layer; The catalyst layer slurry is partially chloromethylated polystyrene, toughening polymer, mono-secondary amine containing double bonds, mono-secondary amine not containing double bonds, initiator, and dehydrating agent completely dissolved in a good solvent; (4) uniformly coating the cathode layer slurry on the catalyst layer of the cation membrane with the catalyst layer and drying it, and separating the PET film after drying to obtain a bipolar membrane; The cathode layer slurry is partially chloromethylated polystyrene, toughening polymer, double-bond monotertiary amine, non-double-bond monotertiary amine, and initiator completely dissolved in a good solvent; (5) Soak the bipolar membrane in a metal ion solution. After soaking, take it out and transfer it to an alkaline solution for transformation.

[0007] As a preferred solution, the step (1) specifically includes the following steps: (11) Prepare an impregnation liquid with styrene, divinylbenzene and initiator, heat it to 30-70°C, completely immerse the mesh in the impregnation liquid, and take out the mesh after soaking for 5-120 minutes. After removing the excess impregnation liquid, lay it flat between two PET films, and seal the edges of the PET films with tape; (12) placing the PET film and the mesh together in a hot water tank for polymerization reaction, taking them out from the hot water tank after the polymerization reaction is completed, and separating the mesh from the PET film; The hot water temperature of the hot water tank is 65-90°C, and the reaction time is 1-15 hours; (13) The separated mesh is placed in the sulfonation liquid of the sulfonation reaction tank for sulfonation reaction. After the sulfonation reaction is completed, the mesh is washed and dried; The temperature of the sulfonation reaction is 30-90° C., and the reaction time is 0.5-10 hours.

[0008] As a preferred solution, the mesh is a woven fabric, a non-woven fabric or a porous film, and is made of low-density polyethylene LDPE, high-density polyethylene HDPE, polyvinyl chloride PVC, polyphenylene sulfide PPS or polyetheretherketone PEEK.

[0009] As a preferred embodiment, in step (11), the impregnation liquid is heated to 40-60° C., and the immersion time is 10-60 minutes; In step (12), the hot water temperature of the hot water tank is 65-80° C., and the reaction time is 3-10 hours; In the step (13), the temperature of the sulfonation reaction is 40-80° C., and the reaction time is 2-4 hours.

[0010] As a preferred embodiment, in step (2), the drying process includes: first drying at 60-90°C for 2-10 hours, and then drying at 90-150°C for 2-10 hours; The preparation process of partially sulfonated polystyrene includes: The sulfonation liquid is added into the polystyrene solution to carry out the sulfonation reaction, the sulfonation reaction temperature is 30-90°C, and the reaction time is 0.5-10 hours; The feed liquid after the sulfonation reaction is completed is added into an ice-water mixture, and the precipitated solid is filtered, washed and dried to obtain partially sulfonated polystyrene.

[0011] As a preferred solution, the step (3) specifically includes: The catalytic layer slurry is sprayed on the partially sulfonated cation membrane, and dried at 60-110° C. for 2-10 hours to obtain a cation membrane with a catalytic layer.

[0012] As a preferred embodiment, the preparation process of the partially chloromethylated polystyrene comprises: Adding chloromethyl ether to a polystyrene solution for chloromethylation reaction at a reaction temperature of 20-60° C. for a reaction time of 1-20 hours to obtain a chloromethylation-completed feed solution; The chloromethylated feed liquid is added into methanol, and the precipitated solid is filtered, washed and dried to obtain partially chloromethylated polystyrene.

[0013] As a preferred embodiment, in step (4), the drying temperature is 60-110° C. and the drying time is 2-10 hours.

[0014] As a preferred embodiment, the dehydrating agent includes at least one of acidic montmorillonite, phosphotungstic acid silicon oxide, and phosphorus pentoxide; The initiator includes at least one of lauroyl peroxide, tert-butyl peroxylaurate, tert-butyl peroxyisobutyrate, benzoyl peroxide, di-tert-butyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

[0015] The present invention also provides a bipolar membrane prepared by the preparation method described in any of the above schemes.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) Compared with the existing bipolar membrane, the bipolar membrane of the present invention enhances the bonding force between the mesh support material and the anode layer and between the cathode and cathode layers, effectively reduces the permeability of anions through the cathode layer and the transmembrane voltage, increases the life of the bipolar membrane, and is conducive to reducing energy consumption and operating costs; (2) The mesh of the present invention adopts a unique hydrophilic modification, and is chemically bonded to the hydrophilic cation layer, which is tightly bonded, and the leakage caused by anions passing through the cation layer is low; (3) The positive layer and the intermediate catalytic layer of the present invention are connected by chemical bonds, and the intermediate catalytic layer and the cathodic layer are connected by chemical bonds. The layers are firmly bonded and will not be easily delaminated like the traditional composite bipolar membrane. In addition, the transmembrane voltage is lower. (4) The present invention adopts a unique cross-linking method of cross-linking after film formation, which makes film formation more controllable and has a higher yield rate; (5) Compared with the conventional monolithic bipolar membrane, the composite bipolar membrane with mesh support of the present invention has higher strength, better dimensional stability and longer service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the cross-sectional structure of the bipolar membrane of Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The bipolar membrane and the preparation method thereof provided by the present invention will be further described below.

[0019] The preparation method of the bipolar membrane of the present invention comprises: performing hydrophilic modification on a mesh cloth by impregnation, polymerization, resulfonation or direct sulfonation to prepare a hydrophilic mesh cloth; using polystyrene as a raw material, performing partial sulfonation to prepare partially sulfonated polystyrene, dissolving the partially sulfonated polystyrene in a good solvent after purification, adding a dehydrating agent, and dissolving to prepare slurry 1; using polystyrene as a raw material, performing partial chloromethylation to prepare partially chloromethylated polystyrene, dissolving the partially chloromethylated polystyrene in a good solvent after purification, and adding a toughening polymer to dissolve to prepare slurry 2; diluting slurry 2 with a good solvent to prepare slurry 3; laying a hydrophilic mesh cloth on a PET film, and evenly coating slurry 1 on the hydrophilic mesh cloth and PE film. On the T film, a cationic membrane with a mesh is prepared; the cationic membrane is cross-linked, which not only achieves the cross-linking within the cation exchange resin, but also achieves the chemical bond connection between the cation exchange resin and the mesh; the slurry 3 is mixed with a mono-secondary amine containing a double bond, a mono-secondary amine without a double bond, an initiator, and a dehydrating agent to prepare a catalytic layer slurry, which is then sprayed on the surface of the cation membrane to prepare an intermediate catalytic layer; the slurry 2 is mixed with a mono-tertiary amine containing a double bond, a mono-tertiary amine without a double bond, and an initiator to prepare a cathodic layer slurry, which is then coated on the intermediate catalytic layer, and after curing, a bipolar membrane is prepared; the prepared bipolar membrane is immersed in a metal ion solution containing hydrolysis catalytic ability, and then deposited and converted to obtain a bipolar membrane with a lower hydrolysis voltage. The interfaces of each layer of the bipolar membrane are clear, the transmembrane voltage is low, the mechanical strength is high, the product qualification rate is high, and the size is stable during use.

[0020] Specifically, the method for preparing a bipolar membrane of the present invention comprises the following steps: 1. Preparation of hydrophilic mesh; a) Material selection: Select mesh fabrics made of materials impregnated with styrene or capable of direct sulfonation. The mesh fabrics may be in the form of woven fabrics, non-woven fabrics, or porous films. The materials include but are not limited to low-density polyethylene (LDPE), high-density polyethylene (HDPE), polyvinyl chloride (PVC), polyphenylene sulfide (PPS), or polyetheretherketone (PEEK). b) Impregnation: Prepare an impregnation liquid with styrene, divinylbenzene and initiator, heat it to 30-70℃, and then completely immerse the mesh in the impregnation liquid to ensure that the mesh is in full contact with the impregnation liquid. Take out the mesh after immersion for 5-120 minutes, remove the excess impregnation liquid, and lay it flat between two PET films. Seal the edges of the PET films with tape; The weight ratio of styrene, divinylbenzene and initiator is 1:0.01-0.4:0.001-0.1; the initiator is mainly a substance capable of forming free radicals, selected from organic peroxides such as lauroyl peroxide, tert-butyl peroxylaurate, tert-butyl peroxyisobutyrate, benzoyl peroxide BPO, di-tert-butyl peroxide, and at least one of azo organic substances such as azobisisobutyronitrile AIBN, azobisisoheptanenitrile ABVN, and dimethyl azobisisobutyrate AIBME; c) Polymerization: Put the PET film and mesh together into a hot water tank for polymerization reaction. The hot water temperature is 65-90°C and the reaction time is 1-15 hours; d) Stripping: After the polymerization is completed, the mesh is taken out from the hot water tank, and the mesh is separated from the PET film. The mesh is used for subsequent reactions; e) Preparation of sulfonation liquid: The sulfonation liquid is a reagent that can introduce sulfonic acid groups on the benzene ring, such as 90-98wt% sulfuric acid, chlorosulfonic acid, a mixture of chlorosulfonic acid and sulfuric acid in a weight ratio of 1:0.1-9, a mixture of acetic anhydride and sulfuric acid in a weight ratio of 1:0.1-1, etc.; f) Sulfonation: first add the sulfonation liquid into the sulfonation reaction tank, then place the mesh cloth of step d) in the sulfonation reaction tank for sulfonation reaction, the reaction temperature is 30-90°C, the reaction time is 0.5-10 hours, and the mesh cloth after sulfonation is first washed in low concentration acid, then washed with clean water and dried for use, thus completing the preparation of the hydrophilic mesh cloth.

[0021] 2. Preparation of partially sulfonated polystyrene; g) Preparation of polystyrene solution: In a stirred reactor, a certain amount of a good polystyrene solvent, such as dichloroethane (DCE), N,N-dimethylformamide (DMF), dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO), etc., is preferentially injected, and polystyrene is added after stirring is started, and the solution is stirred until the polystyrene is completely dissolved and then used for later use; h) Sulfonation: In a stirred reactor, first add a portion of the polystyrene solution prepared in step g) into the reactor, start stirring and start heating, and after reaching the set temperature, slowly add the sulfonation solution in step e) into the reactor. The sulfonation reaction temperature is 30-90° C. and the reaction time is 0.5-10 hours; Wherein, the molar ratio of polystyrene to the sulfonic acid group of the sulfonated liquid is 1:0.1-2; i) Partially sulfonated polystyrene: Add an ice-water mixture into a stirred reactor, start stirring, and slowly pour the sulfonated liquid from step h) into the reactor. Filter and wash the precipitated solids several times, and then dry them for later use. Thus, partially sulfonated polystyrene is prepared.

[0022] 3. Preparation of partially chloromethylated polystyrene; j) Chloromethylation: In a stirred reactor, first add a portion of the polystyrene solution prepared in step g) into the reactor, start stirring and start heating, and after reaching the set temperature, slowly add chloromethyl ether into the reactor. The chloromethylation reaction temperature is 20-60°C and the reaction time is 1-20 hours; Wherein, the molar ratio of polystyrene to chloromethyl ether is 1:0.1-20; k) Partially chloromethylated polystyrene: Methanol is added to a stirred reactor. After stirring, the chloromethylated solution in step j) is slowly poured into the reactor. The precipitated solid is filtered and washed for multiple times, and then dried for later use. Thus, partially chloromethylated polystyrene is prepared.

[0023] 4. Preparation of positive membrane; l) Preparation of cationic membrane slurry: In a stirred reactor, a sulfonated polystyrene good solvent, such as the above-mentioned DCE, DMF, DMAC, DMSO, etc., is preferentially injected. After stirring, the partially sulfonated polystyrene in step i) is first added, and then a dehydrating agent is added. After the polystyrene is completely dissolved, it is used for standby, and is named slurry 1; Among them, the dehydrating agent is mainly a kind of auxiliary agent that can catalyze the dehydration reaction, including acidic montmorillonite, phosphotungstic acid silicon oxide, phosphorus pentoxide, etc.; the weight ratio of partially sulfonated polystyrene to dehydrating agent in the cation membrane slurry is 1:0.005-0.3; m) Cationic membrane coating: The hydrophilic mesh cloth of step f) is spread on the PET film, and then the cationic membrane slurry of step l) is evenly coated on the mesh cloth and the PET film, and then baked at 60-90°C for 2-10 hours, and then baked at 90-150°C for 2-10 hours. After complete drying, a partially sulfonated cationic membrane is prepared.

[0024] 5. Preparation of the intermediate catalytic layer; n) Preparation of partially chloromethylated polystyrene slurry: In a stirred reactor, a good solvent for chloromethylated polystyrene, such as the above-mentioned DCE, DMF, DMAC, DMSO, etc., is preferentially injected. After stirring, the partially chloromethylated polystyrene in step k) is first added, and then a toughening polymer is added. Such polymers may be one or a mixture of more than one of ether bond-containing polymers, amides, lipids, rubbers, etc., and the mixture is set aside after being completely dissolved. The mixture is named slurry 2; o) Preparation of catalytic layer slurry: In a stirred reactor, slurry 2 from step n) is preferentially injected, and after stirring, a certain amount of the good solvent from step n) is added, and after stirring evenly, the slurry is named slurry 3; double bond-containing mono-secondary amine, non-double bond-containing mono-secondary amine, initiator, and dehydrating agent are continuously added to slurry 3, and after they are completely dissolved and stirred evenly, the slurry is set aside; The molar ratio of partially chloromethylated polystyrene, mono-secondary amine containing double bonds, mono-secondary amine not containing double bonds, initiator and dehydrating agent in the catalyst layer slurry is 1: 0.01-0.5: 0.1-0.5: 0.001-0.1: 0.005-0.2; The above-mentioned double-bond-containing mono-secondary amine is selected from at least one of N-methylallylamine and N-ethylmethylallylamine; The above-mentioned mono-secondary amine not containing double bonds is selected from at least one of diethanolamine, di-n-propylamine, diisopropylamine and diethylamine; The initiator comprises at least one of lauroyl peroxide, tert-butyl peroxylaurate, tert-butyl peroxyisobutyrate, benzoyl peroxide, di-tert-butyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate; p) Preparation of catalytic layer: spray the catalytic layer slurry of step o) on the partially sulfonated cation membrane of step m), and then dry it at 60-110°C for 2-10 hours to obtain a cation membrane with a catalytic layer.

[0025] 6. Bipolar membrane preparation; q) Preparation of cathode layer slurry: In a stirred reactor, slurry 2 from step n) is preferentially injected, stirring is started, and then monotertiary amine containing double bonds, monotertiary amine not containing double bonds and initiator are added, and after being completely dissolved and stirred evenly, they are set aside; The molar ratio of partially chloromethylated polystyrene, monotertiary amine containing double bonds, monotertiary amine not containing double bonds, and initiator in the cathode layer slurry is 1: 0.01-0.5: 0.1-0.5: 0.001-0.1; The above-mentioned double-bond-containing monotertiary amine is selected from at least one of N,N-dimethylallylamine, N,N,2-trimethylallylamine, and 3-(dimethylamino)acrylonitrile; The above-mentioned monotertiary amine without double bonds is selected from at least one of triethanolamine, triethylamine, dodecyldimethyl tertiary amine and dioctylmethyl tertiary amine; r) Preparation of bipolar membrane: Place the catalytic layer side of the cation membrane with catalytic layer p) facing upwards, and then evenly coat the cathode material q) thereon, and then dry at 60-110°C for 2-10 hours. After drying, the bipolar membrane is obtained; s) Optimizing the performance of the bipolar membrane: The bipolar membrane of step r) is immersed in a metal ion solution, such as a FeCl2 solution, for a certain period of time, and then the membrane is taken out and immersed in an alkaline solution for transformation to obtain a bipolar membrane with optimized performance.

[0026] The present invention uses a double-bond monoamine (a double-bond mono-secondary amine, a double-bond mono-tertiary amine) to first combine with a chloromethyl group, and then crosslink by double bond polymerization. Compared with the direct combination of a diamine or a polyamine with a chloromethyl group to form a crosslink, it is mainly considered from the perspective of industrialization. If a diamine or a polyamine is used as amination and crosslinking agent, because the reaction rate of the amine and the chloromethyl group is very fast, once the reaction occurs, the crosslinked polymer will quickly precipitate from the solvent, hindering film formation. If you want to form a film smoothly, you must ensure that no reaction occurs before film formation, which is very demanding for the environmental requirements of industrial production. However, when using a double-bond monoamine, this problem does not exist. After the amine and the chloromethyl group are combined, the polymer still exists in a linear form, which will not affect the film formation and is conducive to industrial production.

[0027] In one or more embodiments, the impregnation temperature in the above step b) is 40-60° C. and the time is 10-60 minutes; In one or more embodiments, the polymerization temperature in the above step c) is 65-80° C. and the time is 3-10 hours; In one or more embodiments, the sulfonation reaction temperature in the above step f) is 40-80° C., and the reaction time is 2-4 hours; In one or more embodiments, the sulfonation reaction temperature in the above step h) is 40-80° C., and the reaction time is 2-8 hours; In one or more embodiments, the chloromethylation reaction temperature in the above step j) is 30-50° C., and the reaction time is 2-8 hours; In one or more embodiments, the first stage drying temperature in the above step m) is 70-80°C, the drying time is 4-8 hours, and the second stage drying temperature is 100-140°C, the drying time is 4-8 hours; In one or more embodiments, the drying temperature after spraying the catalytic layer in the above step p) is 70-90°C, and the drying time is 4-8 hours; the immersion temperature of the membrane after drying is 30-50°C, and the immersion time is 0.5-6 hours; the drying temperature after immersion is 40-80°C, and the drying time is 4-8 hours; In one or more embodiments, the drying temperature in the above step r) is 70-90° C., and the drying time is 4-8 hours; In one or more embodiments, the concentration of the metal ion solution in the above step s) is 0.5-5 wt %, the transformation temperature is 25-60° C., and the time is 5-30 min; In one or more embodiments, the metal ion solution in the above step s) can be a combination of one or more of FeCl2, FeCl3, CrCl3, SnCl2, SnCl4, and TiCl4; In one or more embodiments, the alkaline solution in the above step s) can be a strongly alkaline inorganic solution such as NaOH, KOH, etc., with a concentration of 0.5-10 wt%.

[0028] The bipolar membrane and the preparation method thereof of the present invention are further described below by means of specific examples:

[0029] Embodiment 1: The method for preparing the bipolar membrane of this embodiment comprises the following steps: Step 1: Take 1000g of styrene, 140g of divinylbenzene, and 1g of azobisisobutyronitrile, stir and mix at room temperature to prepare an impregnation solution; take a piece of HDPE woven mesh with a thickness of about 0.1mm, completely immerse it in the impregnation solution, heat it to 55°C, and keep it warm for 15 minutes; after the impregnation is completed, take out the mesh, remove the impregnation solution attached to the surface, and lay it flat between two PET films. The edges of the PET films are sealed with tape, and then put it into a hot water tank at 80°C, keep it warm for 5 hours, take it out, separate the mesh from the PET film, and then place the obtained mesh in 98% concentrated sulfuric acid, react at 80°C for 3 hours, wash and dry it to obtain a hydrophilic mesh; Step 2: In a 500mL three-necked flask, inject 250mL DCE, start stirring, add 10g polystyrene, heat to 50°C in a constant temperature water area, slowly drop 98% concentrated sulfuric acid into it after it is completely dissolved, and control the dropping time to add 5mL concentrated sulfuric acid within about 30 minutes. After keeping warm for 5 hours, pour the reaction solution into ice water for precipitation, filter and wash it several times, and then dry it for use; Step 3: In a 500mL three-necked flask, inject 250mL DCE, start stirring, add 10g polystyrene and 0.2g SnCl4, heat to 35°C in a constant temperature water area, slowly add chloromethyl ether after complete dissolution, and control the addition time to add 20mL chloromethyl ether within about 45 minutes. After keeping the temperature for 4 hours, pour the reaction solution into methanol for precipitation, filter and wash it several times, and then dry it for use; Step 4: Take 5 g of the partially sulfonated polystyrene prepared in step 2, dissolve it in 45 mL of DMAC, and after it is completely dissolved, add 0.5 g of acidic montmorillonite, and after it is completely dissolved, prepare slurry 1 for later use; Step 5: Take 5 g of the partially chloromethylated polystyrene prepared in step 3 and 1 g of polyethersulfone, dissolve them in 54 mL of DMAC, and prepare slurry 2 for use after they are completely dissolved; take 10 mL of slurry 2, add 40 mL of DMAC, mix well, and prepare slurry 3, the solid content of which is about 2.0%, for use; Step 6: Lay a PET film on the glass plate, and then lay the mesh obtained in step 1 on the PET film, fix it, and then evenly apply slurry 1 on the mesh and the PET film, and then put it into an oven for drying. The first stage drying temperature is set to 70°C, the drying time is 5 hours, and the second stage drying temperature is set to 120°C, and the drying time is 7 hours; after drying, take out the membrane and the glass plate together for use; Step 7: Place the membrane sheet of step 6 vertically together with the glass plate, take 40 mL of slurry 3 and mix and dissolve with 0.08 g N-methylallylamine, 0.12 g diethanolamine, 0.04 g acidic montmorillonite, and 0.004 g BPO, put them into a sprayer, and spray them on the membrane sheet. After completion, remove the residual slurry at the bottom, place the glass plate horizontally and dry it. The drying temperature is set to 90°C and the drying time is 7 hours. After completion, take it out for use; Step 8: Place the membrane sheet prepared in step 7 horizontally with the surface facing upward, take 30 mL of slurry 2 and mix and dissolve with 0.8 mL of N,N-dimethylallylamine, 1.5 g of triethanolamine, and 0.012 g of BPO, and evenly coat the mixture on the membrane sheet. After completion, place the mixture in an oven for drying at 80°C for 5 hours. After drying, take the mixture out and peel the membrane sheet off the PET to obtain a bipolar membrane. Step 9: In order to further reduce the transmembrane voltage of the bipolar membrane, the membrane obtained in step 8 is directly immersed in a 2wt% FeCl2 solution. After immersion for 1 hour, the membrane is taken out and washed with clean water, and then immersed in an 8wt% sodium hydroxide solution, heated to 40°C, and reacted for 25 minutes for transformation. After the transformation is completed, a bipolar membrane with a lower hydrolysis voltage is obtained.

[0030] like Figure 1 As shown, the bipolar membrane of this embodiment has a three-layer structure, including a cation exchange layer II containing sulfonic acid groups, which is supported by a mesh cloth I with improved hydrophilicity; and an anion exchange layer IV containing quaternary ammonium groups, and between the two layers is an intermediate layer III with water dissociation catalytic ability.

[0031] Embodiment 2: The method for preparing the bipolar membrane of this embodiment is different from that of embodiment 1 in that: step 5 is different from step 7; Specifically, the slurry 3 in step 5 is prepared by taking 5 mL of slurry 2, adding 95 mL of DMAC and mixing, and the solid content of slurry 3 is about 0.5%; Step 7 is to mix and dissolve 40 mL of slurry 3 with 0.02 g of N-methylallylamine, 0.03 g of diethanolamine, 0.01 g of acidic montmorillonite, and 0.001 g of BPO; The other steps are the same as in Example 1.

[0032] Embodiment 3: The method for preparing the bipolar membrane of this embodiment is different from that of embodiment 1 in that: step 5 is different from step 7; Specifically, the slurry 3 in step 5 is prepared by taking 10 mL of slurry 2, adding 90 mL of DMAC and mixing, and the solid content of slurry 3 is about 1.0%; Step 7 is to mix and dissolve 40 mL of slurry 3 with 0.04 g of N-methylallylamine, 0.06 g of diethanolamine, 0.02 g of acidic montmorillonite, and 0.002 g of BPO; The other steps are the same as in Example 1.

[0033] Embodiment 4: The method for preparing the bipolar membrane of this embodiment is different from that of embodiment 1 in that: step 5 is different from step 7; Specifically, the slurry 3 in step 5 is prepared by taking 30 mL of slurry 2, adding 70 mL of DMAC and mixing, and the solid content of slurry 3 is about 3.0%; Step 7 is to mix and dissolve 40 mL of slurry 3 with 0.12 g of N-methylallylamine, 0.18 g of diethanolamine, 0.06 g of acidic montmorillonite, and 0.006 g of BPO; The other steps are the same as in Example 1.

[0034] Embodiment 5: The method for preparing the bipolar membrane of this embodiment is different from that of embodiment 1 in that: step 5 is different from step 7; Specifically, the slurry 3 in step 5 is prepared by taking 30 mL of slurry 2, adding 45 mL of DMAC and mixing, and the solid content of slurry 3 is about 4.0%; Step 7 is to mix and dissolve 40 mL of slurry 3 with 0.16 g of N-methylallylamine, 0.24 g of diethanolamine, 0.08 g of acidic montmorillonite, and 0.008 g of BPO; The other steps are the same as in Example 1.

[0035] Comparative Example 1: The preparation method of the bipolar membrane of this comparative example is different from that of Example 1 in that: Specifically, the mesh is not subjected to hydrophilic modification in step 1, but is directly used for membrane preparation; The other steps are the same as in Example 1.

[0036] Comparative Example 2: The preparation method of the bipolar membrane of this comparative example is different from that of Example 1 in that: Not processed in step 7; The other steps are the same as in Example 1.

[0037] Comparative Example 3: The preparation method of the bipolar membrane of this comparative example is different from that of Example 1 in that: Without processing in step 9; The other steps are the same as in Example 1.

[0038] Comparative Example 4: The preparation method of the bipolar membrane of this comparative example is different from that of Example 1 in that: Not processed by steps 7 and 9; The other steps are the same as in Example 1.

[0039] The bipolar membranes of the above-mentioned Examples 1-5 and Comparative Examples 1-4 were tested respectively below, and the test results are shown in Table 1.

[0040] Among them, the strength of the bonding between the positive and negative layers of the bipolar membrane is characterized by whether bubbles appear, and the method for determining whether bubbles appear is as follows: The membrane was immersed in 4 mol / L NaOH solution at room temperature for 2 hours, then taken out and immediately placed in clean water. If bubbles appeared within 10 minutes, it was judged as foaming; otherwise, it was judged as non-foaming.

[0041] In addition, the permeation test method of the bipolar membrane is as follows: Test device: two hollow cubes with a side length of 8cm and a wall thickness of 1.2cm, one side is not sealed and the other side has a small hole with a diameter of 5mm; place the two hollow cubes with their open sides facing each other, making sure that the side with the small hole faces upwards, then place a sealing gasket on each side of the 8*8cm diaphragm to be tested, and then place it between the hollow cubes, and finally lock the device with an external screw to ensure that the seal is intact and there is no leakage; Test method: Place the above device in water at 25℃, place a small magnetic stirrer at the bottom of the device and in the center of the cube, and place a magnet in each of the two cube containers, then pour 100mL of preheated 4mol / L sodium chloride solution and 100mL of pure water into the two containers respectively, start stirring, stop stirring after 1 hour, and suck out all the solution on the pure water side, rinse with pure water 3 times and suck out all of it, inject all of it into a 250mL volumetric flask to make up the volume, and then take 100mL to test the chloride ion concentration in it to determine the amount of NaCl in the 250mL solution; Table 1 Test results of bipolar membrane ; The permeability of the present invention is characterized by the solute permeability coefficient, which is calculated as follows: ; ; in: σ is the solute permeability coefficient, unit: mmol / (m 2 ·h·mol / L); q is the total amount of sodium chloride permeated into pure water, in mmol; A is the effective area of ​​the test membrane, in m 2 , generally 0.00314m 2 ; Δ C is the concentration difference, in mol / L, i.e. the initial concentration of the permeate is taken as the concentration difference, which is 4 mol / L here; t is the test duration, in hours, usually 1 hour; c Ag is the concentration of silver nitrate standard solution, in mol / L; V is the amount of silver nitrate standard solution consumed during titration, in mL.

[0042] The bipolar membrane diaphragms of the above-mentioned Examples 1-5 and Comparative Examples 1-4 have been tested to have a tensile rupture strength of ≥40MPa and a bursting strength of ≥1.0MPa, which are significantly improved compared to the tensile rupture strength (≤10MPa) and bursting strength (≤0.5Mpa) of the existing single-piece bipolar membrane without mesh support, and the adaptability and life of the membrane are also correspondingly improved.

[0043] It can be seen from Table 1 that as long as the present invention is implemented under appropriate conditions, the transmembrane voltage of the bipolar membrane can be effectively reduced without bubbling, which is beneficial to reducing energy consumption and saving energy.

[0044] In view of the numerous embodiments of the scheme of the present invention, the raw materials and dosage involved can be selected according to actual needs within the limited range, and the experimental data of each embodiment is huge and numerous, which is not suitable for listing and explaining one by one here, but the content required to be verified and the final conclusion obtained in each embodiment are similar. Therefore, the verification content of each embodiment will not be explained one by one here.

[0045] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a bipolar membrane, characterized in that: The following steps are involved: (1) Hydrophilic modification of the mesh to obtain a hydrophilic mesh; (2) Laying the hydrophilic mesh on the PET film, evenly coating the cationic membrane slurry on the mesh and the PET film, and drying to obtain a partially sulfonated cationic membrane; The cation membrane slurry is partially sulfonated polystyrene, and the dehydrating agent is completely dissolved in a good solvent; (3) spraying a catalytic layer slurry on the partially sulfonated cationic membrane and drying the slurry to obtain a cationic membrane with a catalytic layer; The catalyst layer slurry is partially chloromethylated polystyrene, toughening polymer, mono-secondary amine containing double bonds, mono-secondary amine not containing double bonds, initiator, and dehydrating agent completely dissolved in a good solvent; (4) uniformly coating the cathode layer slurry on the catalyst layer of the cation membrane with the catalyst layer and drying it, and separating the PET film after drying to obtain a bipolar membrane; The cathode layer slurry is partially chloromethylated polystyrene, toughening polymer, double-bond monotertiary amine, non-double-bond monotertiary amine, and initiator completely dissolved in a good solvent; (5) Soak the bipolar membrane in a metal ion solution. After soaking, take it out and transfer it to an alkaline solution for transformation.

2. The preparation method according to claim 1, characterized in that: The step (1) specifically includes the following steps: (11) Prepare an impregnation liquid with styrene, divinylbenzene and initiator, heat it to 30-70°C, completely immerse the mesh in the impregnation liquid, and take out the mesh after soaking for 5-120 minutes. After removing the excess impregnation liquid, lay it flat between two PET films, and seal the edges of the PET films with tape; (12) placing the PET film and the mesh together in a hot water tank for polymerization reaction, taking them out from the hot water tank after the polymerization reaction is completed, and separating the mesh from the PET film; The hot water temperature of the hot water tank is 65-90°C, and the reaction time is 1-15 hours; (13) The separated mesh is placed in the sulfonation liquid of the sulfonation reaction tank for sulfonation reaction. After the sulfonation reaction is completed, the mesh is washed and dried; The temperature of the sulfonation reaction is 30-90° C., and the reaction time is 0.5-10 hours.

3. The preparation method according to claim 2, characterized in that: The mesh cloth is a woven cloth, a non-woven cloth or a porous film, and is made of low-density polyethylene LDPE, high-density polyethylene HDPE, polyvinyl chloride PVC, polyphenylene sulfide PPS or polyetheretherketone PEEK.

4. The preparation method according to claim 2, characterized in that: In the step (11), the impregnation liquid is heated to 40-60° C., and the immersion time is 10-60 minutes; In step (12), the hot water temperature of the hot water tank is 65-80° C., and the reaction time is 3-10 hours; In the step (13), the temperature of the sulfonation reaction is 40-80° C., and the reaction time is 2-4 hours.

5. The preparation method according to claim 1, characterized in that: In step (2), the drying process includes: first drying at 60-90°C for 2-10 hours, and then drying at 90-150°C for 2-10 hours; The preparation process of partially sulfonated polystyrene includes: The sulfonation liquid is added into the polystyrene solution to carry out the sulfonation reaction, the sulfonation reaction temperature is 30-90°C, and the reaction time is 0.5-10 hours; The feed liquid after the sulfonation reaction is completed is added into an ice-water mixture, and the precipitated solid is filtered, washed and dried to obtain partially sulfonated polystyrene.

6. The preparation method according to claim 1, characterized in that: The step (3) specifically includes: The catalytic layer slurry is sprayed on the partially sulfonated cation membrane, and dried at 60-110° C. for 2-10 hours to obtain a cation membrane with a catalytic layer.

7. The preparation method according to claim 1, characterized in that: The preparation process of the partially chloromethylated polystyrene comprises: Adding chloromethyl ether to a polystyrene solution for chloromethylation reaction at a reaction temperature of 20-60° C. for a reaction time of 1-20 hours to obtain a chloromethylation-completed feed solution; The chloromethylated feed liquid is added into methanol, and the precipitated solid is filtered, washed and dried to obtain partially chloromethylated polystyrene.

8. The preparation method according to claim 1, characterized in that: In the step (4), the drying temperature is 60-110° C. and the drying time is 2-10 hours.

9. The preparation method according to claim 1, characterized in that: The dehydrating agent includes at least one of acidic montmorillonite, phosphotungstic acid silicon oxide, and phosphorus pentoxide; The initiator includes at least one of lauroyl peroxide, tert-butyl peroxylaurate, tert-butyl peroxyisobutyrate, benzoyl peroxide, di-tert-butyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

10. A bipolar membrane obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of alcohol-soluble quaternary amine type or tertiary amine type anion exchange resin

    CN108080039A

  • Polyethylene / polystyrene composite film roll with screen cloth support and manufacturing method thereof

    CN108752681A

  • Cation exchange membrane with screen cloth reinforced flat-plate-type porous membrane as substrate and manufacturing method of cation exchange membrane

    CN110227561A

  • Composite bipolar membrane and preparation method thereof

    CN118543251A

  • Monolithic bipolar membrane with catalytic layer added on negative membrane surface as well as preparation method and application of monolithic bipolar membrane

    CN118543252A